PERAN DEWAN PENGAWAS SYARIAH DALAM PENGAWASAN OPERASIONAL BAITUL MAAL WAT TAMWIL (STUDI DI BMT ALFA DINAR KARANGANYAR) - Hisyam Faturrahman; Abdul Aziz; Nugraha Prihutama (Journal of Law, Society, and Islamic Civilization, 2015)
At the Baitul Maal wat Tamwil there Sharia Supervisory Board whose function is to oversee the various aspects of sharia in BMT operations and ensure that there is no deviation aspects of sharia in the BMT. Sharia Supervisory Board's role is so important in the BMT, since BMT is an Islamic Financial Micro Institutions. Thus the need for more oversight by the Sharia Supervisory Board in order to gain the trust of the public. On This paper aims want to examine and discuss and analyze the important role of the Sharia Supervisory Board contained in BMT, as well as any obstacles that become obstacles for the Sharia Supervisory Board in performing its duties and authorities.